A Study the small organic Molecule-based Low- Dimensional Nanomaterials with Optoelectronic Properties: Exploring the Functional Properties of Organic Nanostructures (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Over the past few years, research development activity in the vast as well asinterdisciplinary field of nanostructure science technology has exploded globally. Furthermore, theirstrategic place in the 21th century is already set. The field with the earliest beginning most significantsuccesses is the exploration of nanomaterials nanostructures. The study of nanomaterials hasreceived a lot of consideration in both academic industrial research. Nanoscale materials composed offunctional small organic molecules are the focus of this review. For organic nanostructures, we look atthe various approaches that have been taken. Nanostructures ranging from 0D to 1D are studies.